Implementasi Kebijakan dalam Modernisasi Pesantren Darussalam Blokagung dan Relevansinya bagi Pengembangan Pendidikan Formal di Pesantren - Mar Syahid (MOMENTUM : Jurnal Sosial dan Keagamaan, 2020)
Abstract There are three essential points from the final results and conclusions in this research that combines qualitative and quantitative approaches, namely: First, examining the policy model applied by the Darussalam Blokagung Islamic Boarding School Foundation. Second, reviewing the application process, as well as the effectiveness and efficiency of policy implementation at the Darussalam Islamic Boarding School Foundation. The two points above are analyzed to produce a complete concept related to policies in modernization which are applied at the Darussalam Islamic Boarding School Foundation. The results of the analysis provide a conceptual basis for developing the theory of pesantren policies in developing formal educational institutions. The goal is for the next point, Third, to formulate a prototype of a boarding school policy that can be applied at other Pondok Peesantren Foundations that establish or develop formal education from SD / MI to Higher Education (PT). Education that integrates Islamic knowledge and general knowledge which is accommodated by the Indonesian government.